Is Strip Cropping an Effective Way for Maize Biofortyfication? - Aleksandra Głowacka; Bogdan Szostak; Renata Klebaniuk; Anna Kiełtyka-Dadasiewicz (Journal of Chemistry)
The aim of the study was to assess the impact of strip cropping on the content of nitrogen, phosphorus, potassium, magnesium, and calcium in maize. A field experiment was conducted during 2008–2010 in South Poland. The two cropping methods of maize were studied: sole cropping and strip cropping with common bean and spring barley. Maize was harvested in two different cycle stages: for silage in milky-wax phase and for grain in full maturity phase. Strip cropping significantly increased the accumulation of Mg and Ca by maize biomass and grain. However, the phosphorus content was higher only in maize grain. The row position in the strip influenced the macronutrients content in maize biomass and in grain. The placement adjacent to the bean resulted in higher Ca and Mg content in maize biomass and in grain. The phosphorus content in maize grain was also significantly higher in neighbouring rows with common bean strip. The least amounts of P and N were found in maize from the row adjacent to the barley strip. The results obtained indicated that strip cropping of maize with appropriate plant species, especially pulses, that is, common bean, seems to be an effective way to biofortify maize grain with Ca, especially in regions where it is the staple food. Furthermore, this may mitigate the deficiency of Mg and Ca in maize forage.